2016
DOI: 10.1063/1.4961667
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-graphene composite film as transparent conductive electrode for GaN-based light-emitting diodes

Abstract: Transparent conductive electrodes (TCE) made of carbon nanotube (CNT) and graphene composite for GaN-based light emitting diodes (LED) are presented. The TCE with 533-/sheet resistance and 88% transmittance were obtained when chemical-vapor-deposition (CVD) grown graphene was fused across CNT networks. With an additional 2-nm thin NiOx interlayer between the TCE and top p-GaN layer of the LED, the forward voltage was reduced to 5.12 V at 20-mA injection current. Moreover, four-fold improvement in terms of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Heterostructures of two dimensional layered materials and wide band gap semiconductors are of great importance for optoelectronic and nanoelectronic applications . Among the wide band gap semiconductors, gallium nitride (GaN) is one of the most attractive nitride semiconductor for applications in light‐emitting diodes (LEDs), solar cells, photodetectors, high‐electron‐mobility transistors, and high frequency power devices . Recently, significant interest has been given to fabricate graphene/GaN based Schottky junction considering the outstanding properties of both the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Heterostructures of two dimensional layered materials and wide band gap semiconductors are of great importance for optoelectronic and nanoelectronic applications . Among the wide band gap semiconductors, gallium nitride (GaN) is one of the most attractive nitride semiconductor for applications in light‐emitting diodes (LEDs), solar cells, photodetectors, high‐electron‐mobility transistors, and high frequency power devices . Recently, significant interest has been given to fabricate graphene/GaN based Schottky junction considering the outstanding properties of both the materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the composites or hybrid materials based on graphene and carbon nanotube (CNT) have become a subject of extensive studies since synergistic effects of such kind of combination allowed for a significant progress in the development of novel flexible transparent electrodes [1][2][3], supercapacitors [4,5], and sensitive biological sensors [6]. It was demonstrated, for example, that in a polymer composite the presence of CNTs prevented aggregation of graphene nanoparticles and, on the other hand, graphene nanoparticles improved the dispersion of CNTs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [3,11], it was shown that the presence of a small number of CNTs on the surface of chemical-vapor-deposited (CVD) graphene results in a significant decrease of the sheet resistance, keeping the optical transmittance at the same level.…”
Section: Introductionmentioning
confidence: 99%
“…The TCEs of multiwall carbon nanotubes (MWCNTs) incorporated with graphene quantum dots were made for GaN-based light emitting diodes (LED). A sheet resistance of 533 Ω and a transmittance of 88% were obtained when chemical-vapor-deposition grown graphene was fused across CNT networks [10]. Recently [11], we have prepared composite films of poly(3-hexylthiophene) and reduced graphene oxides (rGO-P3HT) for sensing ammonia gas.…”
Section: Introductionmentioning
confidence: 99%